(untitled) (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
Human resources (HR) managers are among the industries in which IOT is ongoing to have a big influence The HR manager is in charge of identifying and employing the most qualified applicants for a place, and use of AI in HR can significantly influence recurting and HR management procedures. The automation of repetitive process, such artificial intelligence on human resources of the biggest impacts of artificial intelligence on human resources the efficiency of the candidate screening procedure can be increased and the possibility of hum an error decreased with software solutions that rely on machine learning algorithms and data analysis. Examining the advantages and disadvantages of artificial intelligence for human response is the aim of the paper.